Recycling of Date-Palm Fiber to Produce Pleurotus Cornucopiae Var. Citrinopileatus Mushroom - Owaid, Mustafa Nadhim; Saleem Al-Saeedi, Sajid Salahuddin; Abed, Idham Ali (International Journal of Environment, 2017)
In this study, some local available organic matters, which are including wheat straw (Triticum aestivum), sawdust, and fiber of date palm (Phoenix dactylifera L.), were used for growing and cultivating of bright yellow oyster mushroom Pleurotus cornucopiae var. citrinopileatus. The possibility of using date palm fiber (in mixtures with other organic residues) as a substrate for the cultivation and production of fruiting bodies of P. cornucopiae var. citrinopileatus was investigated. This mushroom is capable of biorecycling and utilization of some mixtures of lignocellulosic substrates successfully, especially the mixture S3 (50% wheat straw, 30% sawdust, and 20% date palm fiber). The lower mycelia completion time was 17 days, that shown in bags of the S3 substrate. Date-palm fiber substrate exhibited best growth intensity level (moderate) significantly (p<0.05). The total yield and biological efficiency percent recorded approx. 90 g and 23% on the S3 substrate respectively, as a higher percent significantly (p<0.05), while sawdust substrate alone was an unsuitable medium for cultivation and production of this mushroom. Finally, the use of date-palm fibers in mixtures is usefulness in producing a fresh edible and medicinal mushroom. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-4, Sep-Nov 2016, page: 56-65